2014
DOI: 10.1371/journal.pone.0088173
|View full text |Cite
|
Sign up to set email alerts
|

The Antibody Response of Pregnant Cameroonian Women to VAR2CSA ID1-ID2a, a Small Recombinant Protein Containing the CSA-Binding Site

Abstract: In pregnant women, Plasmodium falciparum-infected erythrocytes expressing the VAR2CSA antigen bind to chondroitin sulfate A in the placenta causing placental malaria. The binding site of VAR2CSA is present in the ID1-ID2a region. This study sought to determine if pregnant Cameroonian women naturally acquire antibodies to ID1-ID2a and if antibodies to ID1-ID2a correlate with absence of placental malaria at delivery. Antibody levels to full-length VAR2CSA and ID1-ID2a were measured in plasma samples from 745 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Thus, O'Neil-Dunne et al (40) showed that CSA adhesion-inhibitory plasma Abs were generally absent early in pregnancy but increased steadily toward delivery, and this increase occurred earlier and faster in multigravidae than in primigravidae. Other studies have yielded similar results (30,41,42). However, it should be emphasized that the overall trend obviously masks transient responses where levels increase, then decline before delivery in some (mainly multigravid) women (43) or show more complex dynamics (26).…”
Section: Discussionmentioning
confidence: 56%
“…Thus, O'Neil-Dunne et al (40) showed that CSA adhesion-inhibitory plasma Abs were generally absent early in pregnancy but increased steadily toward delivery, and this increase occurred earlier and faster in multigravidae than in primigravidae. Other studies have yielded similar results (30,41,42). However, it should be emphasized that the overall trend obviously masks transient responses where levels increase, then decline before delivery in some (mainly multigravid) women (43) or show more complex dynamics (26).…”
Section: Discussionmentioning
confidence: 56%
“…A recent study showed that the response to ID1-ID2a, which spans the DBL2 domain (central core of the DBL1X-3X region), is not recognized specifically during pregnancy (22). Indeed, antibody levels did not change during the course of pregnancy and did not increase with gravidity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study also performed in Cameroon but on a larger number of pregnant women revealed that the response to ID1-ID2a (which span the DBL2 domain) was not pregnancy specific but predominantly directed against unrelated cross-reactive epitopes which may have been induced by other PfEMP1 variants during previous infections (22).…”
mentioning
confidence: 99%
“…Previous studies evaluating the influence of IPT measured Abs that bound to the surface of CSA-binding IE 15,16,23,25,34 or DBL5 24,34 in cohorts of women consisting of either primigravidae alone or a combination of primigravidae and multigravidae. Thus, the direct influence of IPT on multigravidae has not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Samples collected at delivery or late in the third trimester were screened in the avidity assay from FV2-seropositive women as previously described. 34 In brief, plasma was diluted 1:300, 1:1,000 and 1:3,000 in 1% BSA-PBS, and 50 μL of diluted plasma was added to 50 μL of FV2-coupled microspheres (2,000 microspheres per test). After incubation for 1 hour, beads were washed and half of the paired beads were resuspended in 100 μL of 3M NH 4 SCN in 1% BSA-PBS and in 100 μL of 1% BSA-PBS.…”
Section: Methodsmentioning
confidence: 99%